Assessment of land use /land cover changes using Landsat data series: A case study of Chandauli district - Goswami, Kaushalendra Prakash; Yadav, Sushil Kumar; Shekher, Himanshu (National Geographical Journal of India, 2022)
The rapid growth of population, urbanization, economic activities and natural phenomena have affected and simultaneously changed the land use land cover pattern. The main aim of this study is to gain a quantitative understanding of land use land cover changes in Chandauli district from 2000 to 2019. The maximum likelihood supervised classification in ERDAS imagine and ARC GIS software is applied in this study for the preparation of land use land cover maps and analysis of the pattern of land cover through satellite data for the years 2000, 2010 and 2019. The classification of land use land cover is divided into nine major classes i.e. water bodies, sand, cropland, built-up land, fallow land, wasteland, dense forest, open forest and scrub forest. Change detection analysis was also included in this analysis. The general pattern of LULC in this area includes an expansion of Fallow land (18.31 per cent), built-up land (13.43 per cent), open forest and water bodies as well as a reduction in the wasteland (12.59 per cent) and dense forest areas in the reference period (2000-2019). The result also indicates that the dominating forest cover exists in southern Chandauli district. The mapping of land use land cover classes is also helpful in the study of change detection and natural resource management.